Temporal patterns of protozooplankton abundance and their food in Ellis Fjord, Princess Elizabeth Land, eastern Antarctica - Grey, J; Laybourn-Parry, J; Leakey, RJG; Andrew McMinn (1997)
The abundance and biomass of ciliates, dinoflagellates and heterotrophic and phototrophic nanoflagellates were determined at three sites along an ice-covered Antarctic fjord between January and November 1993. The water column showed little in the way of temperature and salinity gradients during the study period. In general, the protozooplankton exhibited a seasonal variation which closely mirrored that of chlorophyll Î± and bacterioplankton. The fjord mouth, which was affected by the greatest marine influences, consistently had the highest densities of ciliates and the most diverse community, with up to 18 species during the sampling period. Small aloricate ciliates were present throughout the year with Strobilidium spp. being dominant during the winter. Larger loricate and aloricate ciliates became more prominent during January and November, along with the autotrophic ciliate Mesodinium rubrum and two mixotrophic species (Strombidium wulffi and a type resembling Tontonia) suggesting evidence of species successions. Data on dinoflagellates were less extensive, but these protists showed greatest species diversity in the middle reaches of the fjord. A total of 13 species of dinoflagellate was recorded. Ciliates made a significant contribution to the biomass of the microbial community in summer, particularly in the middle and at the seaward end of the fjord. In winter, heterotrophic flagellates (HNAN) and phototrophic nanoflagellates (PNAN) were the dominant component of protistan biomass. In terms of percentage contribution to the microbial carbon pool, bacteria dominated during winter and spring. To the author's knowledge, this is the first seasonal study of an Antarctic fjord. The Ellis Fjord is very unproductive compared to lower latitude systems, and supports low biomass of phytoplankton and microbial plankton during most of the year. This relates to severe climatic and seasonal conditions, and the lack of allochthonous carbon inputs to the system. Thus, high latitude estuaries may differ significantly from ...